Eksplorasi Sejarah, Arsitektur, dan Konservasi Candi Tebing Tegallinggah sebagai Warisan Budaya di Gianyar, Bali - Fadillah Manuhutu; Nurfadillah Mustari; I Wayan Sugita; Putu Ayu Dian Ratna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The objective of this research is to critically evaluate the historical significance, architectural features, and conservation techniques associated with the Tegalinggah Cliff Temple, a major cultural heritage site in Gianyar, Bali. The inquiry used a qualitative research technique, collecting primary data through field observations and interviews with historians, local community stakeholders, and conservation specialists, supported with secondary material from relevant academic literature. Data was analyzed using qualitative descriptive approaches, supplemented by focus group discussions, to offer a thorough knowledge of the temple's historical background, architectural elements, and contemporary conservation efforts. The research results show that, despite Tegalinggah Cliff Temple's historical and architectural significance, it faces serious preservation issues such as natural degradation and limited community participation. The report emphasizes the importance of enhanced local engagement and the establishment of stronger conservation management structures to protect the site. In conclusion, the Tegalinggah Cliff Temple is an important cultural asset that requires increased preservation measures to maintain the long-term protection and development of Balinese cultural heritage.